Pengaruh Akuntansi Forensik, Audit Investigatif, Dan Independensi Auditor Terhadap Pengungkapan Fraud - Khofidah Pujilestari; Nera Marinda Machdar (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2024)
This article examines the influence of forensic accounting, investigative auditing, and auditor independence on fraud disclosure. The aim is to create a hypothesis regarding the influence of each variable that will be used in future research. The results of this literature review are: Forensic Accounting, Investigative Auditing, and Auditor Independence influence Fraud Disclosure.